Can Urban Local Ponds Help Tackle Domestic Water Scarcity and Build Resilience? with Reference to South Asian Cities and City Regions - Ripin Kalra (Journal of Regional and City Planning, 2020)
For decades to come, cost-effective and environmentally appropriate water systems will be a priority for managing water scarcity and building resilience in the rapidly expanding cities and city regions of South Asia. This study initiates a research into urban local ponds and the potential of linking them with water systems and build resilience. A framework of questions guided the research with reference to ponds and prevalent water systems in South Asian cities and city regions. The wider issues of water stress in South Asian cities and the general limitations of prevalent water supply systems were studied through the lens of a literature review. The paper then draws upon observations in three South Asian cities. The research showed that despite policy support for local rainwater capture, groundwater is over-exploited and urban local ponds (and tanks) have not been integrated with urban water provision schemes, particularly in recent decades. It was concluded that local urban ponds can facilitate resilient water-supply provision by making them an integral part of the urban waterscape. This paper highlights a multitude of benefits that ponds can potentially bring to urban resilience, in particular affordable and accessible water provision with low environmental footprint, managing climate shocks or stresses, biodiversity restoration in urban areas as well as potentially generating new skills and livelihoods for communities. The overall suggestion is that local urban ponds should be networked into the water provision for cities and their wider region, thereby linking to wider arrangements for urban and regional governance and resilience.Abstrak. Dalam beberapa dekade mendatang, sistem air yang hemat biaya dan ramah lingkungan akan menjadi prioritas untuk mengelola kelangkaan air dan membangun ketangguhan di kota-kota yang berkembang pesat dan kawasan perkotaan di Asia Selatan. Makalah ini memulai penelitian mengenai kolam lokal perkotaan, dan potensi untuk menghubungkannya dengan sistem air dan membangun ketangguhan. Kerangka pertanyaan memandu penelitian ini dengan mengacu pada kolam dan sistem air yang umum di kota-kota Asia Selatan dan kawasan kota. Isu yang lebih luas mengenai persoalan air di kota-kota Asia Selatan dan keterbatasan sistem penyediaan air yang umum dipelajari melalui tinjauan literatur. Makalah ini kemudian mengacu pada pengamatan di tiga kota di Asia Selatan. Penelitian menunjukkan bahwa meskipun ada dukungan kebijakan untuk penangkapan air hujan lokal, air tanah dieksploitasi secara berlebihan dan kolam lokal perkotaan (dan tangki) tidak terintegrasi dengan skema penyediaan air perkotaan, terutama dalam beberapa dekade terakhir. Disimpulkan bahwa kolam lokal perkotaan dapat memfasilitasi penyediaan pasokan air yang tangguh dengan menjadikannya sebagai bagian integral dari lanskap perairan perkotaan. Makalah ini menunjukkan bahwa banyak potensi manfaat kolam untuk ketangguhan perkotaan, khususnya dalam penyediaan air yang terjangkau dan dapat diakses dengan jejak lingkungan yang rendah, mengelola gegar atau tekanan iklim, pemulihan keanekaragaman hayati di daerah perkotaan serta berpotensi menghasilkan keterampilan dan mata pencaharian baru bagi masyarakat. Saran keseluruhan adalah bahwa kolam lokal perkotaan harus disambungkan ke dalam sistem penyediaan air untuk kota dan wilayah yang lebih luas, sehingga menghubungkannya dengan pengaturan yang lebih luas untuk tata kelola dan ketangguhan perkotaan dan regional.Kata kunci. Kolam, ketangguhan perkotaan, air permukaan, jaringan air, tata kelola air, transfer air regional.